Multiple Mitogen-Activated Protein Kinase Signaling Pathways Connect the Cot Oncoprotein to the c-jun Promoter and to Cellular Transformation - Chiariello, Mario (American Society for Microbiology, 2000)
The serine/threonine kinase Cot is a member of the mitogen-activated protein kinase (MAPK) kinase kinase family implicated in cellular transformation. Enhanced expression of this protein has been shown to activate both the MAPK and the c-Jun N-terminal kinase (JNK) pathways and to stimulate the nuclear factor of activated T cells and NF-κB-dependent transcription. However, the nature of the normal functions of the Cot protein and the molecular mechanisms responsible for its oncogenic potential are still largely unknown. Here, we show that overexpression of the cot proto-oncogene is sufficient to stimulate the expression of c-jun and that, in turn, the activity of c-Jun is required for Cot-induced transformation. These observations prompted us to explore the molecular events by which Cot regulates c-jun expression. We found that Cot potently stimulates the activity of the c-jun promoter utilizing JNK-dependent and -independent pathways, the latter involving two novel members of the MAPK family, p38γ (ERK6) and ERK5. Molecularly, this activity was found to be dependent on the ability of Cot to activate, in vivo, members of each class of the MAPK kinase superfamily, including MEK, SEK, MKK6, and MEK5. Furthermore, the use of dominant interfering molecules revealed that Cot requires JNK, p38s, and ERK5 to stimulate the c-jun promoter fully and to induce neoplastic transformation. These findings indicate that Cot represents the first example of a serine/threonine kinase acting simultaneously on all known MAPK cascades. Moreover, these observations strongly suggest that the transforming ability of Cot results from the coordinated activation of these pathways, which ultimately converge on the regulation of the expression and activity of the product of the c-jun proto-oncogene.